The international law on foreign investment - Sornarajah, M. (Cambridge University Press, 2004)
This new edition of Sornarajah's book, available for the first time in paperback, surveys the international law developed to protect foreign investment by multinational corporations. The area has always been one of controversy due to the different political and economic conflicts that exist in the field. The book assesses the role of multinational corporations in making foreign investments, and considers the ways in which misconduct on the part of such corporations in host states could be controlled. Sornarajah focuses on the protection of foreign investment and the problems associated with such protection. He explores treaty-based methods, and examines several bilateral and regional investment treaties. The failure to agree on a multilateral treaty system and the inability to incorporate a discipline on investment within the WTO are also considered. He takes account not only of the law, but also of the relevant literature in economics, political science and other associated disciplines